1986
DOI: 10.1017/s000335610001816x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pigs with or without the intestinal receptor forEscherichia coliK88

Abstract: The adhesion of Escherichia (E.) coli K88ac to epithelial cells of the small intestine was studied after slaughter in 564 crossbred pigs (Swedish LandracexSwedish Yorkshire). E.coli K88ac adhered to epithelial cells obtained from different parts of the small intestine in 40·8% of the pigs studied. Performance data indicated that presence of the receptor resulted in poorer daily gain during the 1st weeks of life, but that it had a beneficial influence on daily lean growth during the fattening period (24 to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
1
31
1
Order By: Relevance
“…They performed the adhesion assay by incubating single enterocytes with bacteria as described by Edfors-Lilja et al (1986). Ten to 20 epithelial cells were examined for adhesion by interference contrast microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…They performed the adhesion assay by incubating single enterocytes with bacteria as described by Edfors-Lilja et al (1986). Ten to 20 epithelial cells were examined for adhesion by interference contrast microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…High costs, laboriousness and the fact that pigs have to be slaughtered and, therefore, cannot be used for breeding purposes are serious drawbacks for the common adhesion tests to be used on large scale, as is also discussed for selection on E. coli-F18 resistance [30,31]. Moreover, it is debatable whether it is advisable to breed out a trait that might have an unknown beneficial function [32,33] or that will change the selection pressure on pathogenic E. coli. We calculated that, assuming that the transmission from F4Rx piglets to other piglets is 0, the maximum fraction of F4R+ piglets should be 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Huang (1977) found no evidence of an association between early growth in pigs and ability to develop humoral immune response to synthetic antigens. Higher gains and feed efficiency were found by Edfors-Lilja et al (1986) to be related to susceptibility to K88 E. coil scours. Correlations of production traits and immune response to PR and B. bronchiseptica vaccines from this study are shown in table 6.…”
Section: Resultsmentioning
confidence: 89%
“…A primary component of disease resistance is the humoral immune response (Gavora and Spencer, 1983 ;Buschmann et al, 1985;Warner et al, 1987 (Buschman et al, 1974), hen egg white lysozyme (Vaiman et al, 1978), E. coli vaccine (Edfors-Lilja et al, 1984, 1985, Bordetella bronchiseptica vaccine (Rothschild et al, 1984a) and pseudorabies vaccine (Rothschild et al, 1984b). Little is known about the relationships among immune response traits and production traits (Rothschild, 1985;Edfors-Lilja et al, 1986).…”
Section: Introductionmentioning
confidence: 99%